Anatomical study of the cervical nerve roots for posterior foraminotomy: cadaveric study - Barakat, Mohamed (Springer-Verlag, 2012)
BACKGROUND: Anatomical study of the relationship among the cervical nerve roots, intervertebral disc, and lateral mass is important for the neurosurgeon to avoid complications of posterior cervical foraminotomy. METHODS: Six adult cadavers were studied. The muscles of the back of the neck were removed to expose the cervical vertebrae posteriorly from C3 to C7. We measured the length, height, extent, and angulations of the nerve roots from the medial point of the facet (MPF) after a total laminectomy, then after one-half facetectomy. The height, width, anteroposterior diameter of the lateral mass, then the height and anteroposterior diameter of the neural foramen were also measured. RESULTS: After total laminectomy from C3 to C7, all measures were taken from MPF showed that the mean length of the exposed root was 6.5–8.8 mm while vertical distance was 4–5.4 mm and the horizontal distance was 5.1–7.1 mm. Following a medial one-half facetectomy; the mean length of the exposed root was 8.9–12.3 mm, the vertical distance was 5.5–7.3 mm while the horizontal distance was 7.1–9.8 mm. The mean angulations of the nerve roots were 50.9–53.3º. There was a significant difference after total laminectomy and medial one-half facetectomy. CONCLUSION: Anatomic and morphologic study of the cervical nerve roots and their relationships to the lateral mass and the intervertebral disc are useful landmarks to reduce the operative complications of the posterior foraminotomy.